Breaking Mental Barriers Promotes Recovery After Spinal Cord Injury - Rodocker, Haven I.; Bordbar, Arman; Larson, Molly J. E.; Biltz, Rebecca G.; Wangler, Lynde; Fadda, Paolo; Godbout, Jonathan P.; Tedeschi, Andrea (Frontiers in Molecular Neuroscience, 2022)
Functional recovery after spinal cord injury (SCI) often proves difficult as physical and mental barriers bar survivors from enacting their designated rehabilitation programs. We recently demonstrated that adult mice administered gabapentinoids, clinically approved drugs prescribed to mitigate chronic neuropathic pain, recovered upper extremity function following cervical SCI. Given that rehabilitative training enhances neuronal plasticity and promotes motor recovery, we hypothesized that the combination of an aerobic-based rehabilitation regimen like treadmill training with gabapentin (GBP) administration will maximize recovery in SCI mice by strengthening synaptic connections along the sensorimotor axis. Whereas mice administered GBP recovered forelimb functions over the course of weeks and months following SCI, no additive forelimb recovery as the result of voluntary treadmill training was noted in these mice. To our surprise, we also failed to find an additive effect in mice administered vehicle. As motivation is crucial in rehabilitation interventions, we scored active engagement towards the rehabilitation protocol and found that mice administered GBP were consistently participating in the rehabilitation program. In contrast, mice administered vehicle exhibited a steep decline in participation, especially at chronic time points. Whereas neuroinflammatory gene expression profiles were comparable between experimental conditions, we discovered that mice administered GBP had increased hippocampal neurogenesis and exhibited less anxiety-like behavior after SCI. We also found that an external, social motivator effectively rescues participation in mice administered vehicle and promotes forelimb recovery after chronic SCI. Thus, not only does a clinically relevant treatment strategy preclude the deterioration of mental health after chronic SCI, but group intervention strategies may prove to be physically and emotionally beneficial for SCI individuals.